Review of functional in vitro models of the blood-cerebrospinal fluid barrier in leukaemia research - Erb, Ulrike; Schwerk, Christian; Schroten, Horst; Karremann, Michael (Journal of neuroscience methods, 2020)
Acute lymphoblastic leukaemia represents the most common paediatric malignancy. Although survival rates approach up to 90% in children, investigation of leukaemic infiltration into the central nervous system (CNS) is essential due to the presence of ongoing fatal complications. Recent in vitro studies mostly employed models of the blood-brain barrier (BBB), as endothelial cells of the microvasculature represent the largest surface between the blood stream and the brain parenchyma. However, crossing the blood-cerebrospinal fluid barrier (BCSFB) within the choroid plexus (CP) has been shown to be a general capability of leukaemic blasts. Hence, in vitro models of the BCSFB to study leukaemic transmigration may be of major importance to understand the development of CNS leukaemia. This review will summarise available in vitro models of the BCSFB employed to study the cellular interactions with leukaemic blasts during cancer cell transmigration into the brain compartment across primary or immortal/immortalised BCSFB cells. It will also provide an outlook on prospective improvements in BCSFB in vitro models by developing barrier-on-a-chip models and brain organoids.
Gesehen am 20.02.2020
Available online 24 October 2019